Comparing the corrosion protection performance of graphene nanosheets and graphene quantum dots as nanofiller in epoxy coatings. Issue 5 (6th August 2019) - Pourhashem, Sepideh; Rashidi, Alimorad; Vaezi, Mohammad Reza
Abstract : Purpose: In this research, the effect of graphene nanosheets and graphene quantum dots (GQDs) as carbon-based nanofillers on corrosion protection performance of epoxy coatings is considered. Design/methodology/approach: Graphene nanosheets are synthesized via chemical vapor deposition method, and GQDs are synthesized by a simple and gram scale procedure from carbon black. The prepared nanofillers are characterized by X-ray diffraction technique, Fourier transform infrared spectroscopy and transmission electron microscopy. Further, solvent-based epoxy coatings containing 0.1 Wt.% graphene nanosheets and GQDs are prepared, and the corrosion resistance of nanocomposite coatings is considered by electrochemical impedance spectroscopy. Findings: The results indicate that both epoxy/graphene nanosheets and epoxy/GQDs samples have significantly higher corrosion resistance than pure epoxy coating. Meanwhile, GQDs can more effectively enhance the corrosion protection performance of epoxy coatings compared to graphene sheets, which can be attributed to the presence of functional groups on GQDs and improving the dispersion quality in polymer matrice. Originality/value: In this research, for the first time, the graphene quantum dots (GQDs) prepared by a "top-down" method from carbon black are used as nanofiller in epoxy coatings, and the potential application of graphene nanosheets and GQDs as anti-corrosion nanofiller in epoxy coatings is investigated.